Optimization of the Death Penalty in National Criminal Law - Dino Rizka Afdhali; Yanto Yanto; Slamet Tri Wahyudi (International Journal of Sociology and Law, 2025)
Under Law No. 1 of 2023 or the New Criminal Code, capital punishment is regulated as a punishment that involves the deprivation of the defendant's life for serious crimes committed, with its implementation following the procedural rules for capital punishment in Indonesia. The provisions outlined in Article 67 of the New Criminal Code specify the application of capital punishment in Indonesia, stating that it is no longer the primary punishment but rather the last resort after a ten-year probationary period. This study uses a normative legal method with legal sources such as primary legal materials, namely laws regulating capital punishment, as well as secondary legal materials, which explain and clarify the primary laws. The debate on capital punishment involves two main schools of thought, namely those who support the application of capital punishment for serious crimes and those who reject the application of capital punishment due to the human rights perspective adopted by the Indonesian state. Criticism of the death penalty includes issues of the right to life and the legal treatment that should be given by the government to defendants for extraordinary crimes, especially in cases of corruption, premeditated murder, and narcotics. In this study, it was found that (1) the optimal form of regulation of the death penalty for extraordinary crimes has actually been implemented quite well, but the execution of the death penalty is still considered weak by the author because the execution must be preceded by a waiting period of several years in prison for the condemned prisoner (2) that the death penalty is not contrary to human rights, whether viewed from a legal, religious, or international perspective. (3) The new Criminal Code can balance the retributive and rehabilitative aspects as the ideal concept for the implementation of the death penalty. However, in some provisions, it is hoped that the death penalty can be used as a Premium Remedium in certain cases.